The use of mixed bomass alga-fungi in mutualistic relationship and natural marine-origin carrier in MBBR reactor for an ecological treatment of effluents from fish processing industry in Morocco - Ikrame Charef; Asmaa Fathi; Fatima Zahra Ozi; Zakaria Asbai; Ghita Radi Benjelloun; Khawla Waddi; Bouchaib Bahlaouan; Said El Antri; Nadia Boutaleb (Desalination and Water Treatment)
The biological treatment in a fluidised biofilm bed bioreactor (MBBR) of fisheries effluent was studied using a mixed biomass of macro-algae and Aspergillus niger as fungal innoculum. The Green macro algae Ulva lactuca (ULva) and the Brown seaweed genus of Laminaria collected from the coast of Mohammedia city in Morocco, was used to ensure better efficiency in reducing pollution in the cases of mixed biomass bioreactor and of a mutualistic relationship favorable between Algae and fungi. For better ecological and economic advantages this study also considers the biofilm colonization media used and also compared between the use of conventional Kaldnes K3 and sardine scales as a support for biofilm colonization in MBBR bioreactors. The results obtained showed that the use of co-culture of fungi and macro-algae represents an excellent development prospect. The organic substance reduction efficiency obtained in this study, using the mixed biomass between the brown macro alga laminaria and the Aspergillus niger fungi, is better than that obtained by using the biomass containing the green macro alga, especially for the reduction of total nitrogen, so that the abatement rate is up to 78% for the natural sardine shell support and 72% for the synthetic K3 support.